Pemberdayaan UMKM Komunitas OK OCE Menggunakan Media Digital - Rully Mardjono; Laser Narindro; Adrian Sjamsul Qamar; Syandra Sari; Arfa Maulana; Ida Jubaidah (Abdimas Universal, 2022)
For support development oaf real sector economy, the efforts which needed to foster Micro, Small And Medium Enterprises (MSMEs) in running their business units, we should to provide knowledge and skills to MSME actors for running and develope their business units. Based on that things, OK OCE team which collaboration with Informatics Engineering Major, Trisakti University carried out skills training in the form of using the okeoce.net website application through the Community Service Program, the aim that MSME actors can have the skills to create a portfolio of business units and collect data through a website application for mentoring and coaching efforts. The method used in this acivity are seminar and workshop for using of okeoce.net website with implementation method by online. From the results of the training assessment through online questionnaires, 90.26% considered that they are understand and very satisfied with the materials and methods provided during training. With the MSME data in the website, it can be used as basis data  for decision making for policy makers to analyze and mapping for MSME data based on their types and needs to determine strategic policies for development of curriculum and training materials for MSME development strategies.